Evolution of emollients and active ingredients in dermatology - D.V. Kozlova; D.V. Zaslavsky; A.V. Taganov; S.F. Kayumov (Russian Journal of Clinical Dermatology and Venereology, 2026)
Emollients are the fastest-growing class of cosmeceuticals. This is due to the growing number of patients with conditions requiring constant skin care, accompanied by epidermal barrier dysfunction and inflammation (e.g., xerosis, atopic dermatitis, psoriasis, seborrheic dermatitis). Nevertheless, diagnosis and management of patients with xerosis cutis remain poorly standardized. Modern studies have deepened our knowledge of the molecular composition within a multifaceted understanding of the epidermal barrier as an integral system. This has enabled the introduction of numerous active ingredients into cosmeceuticals to deliver anti-inflammatory, antioxidant, antimicrobial, and antipruritic effects. In recent years, a new approach to the treatment of dermatoses accompanied by xerosis, based on the use of so-called «emollients plus», has been developed. A new class of «smart» emollients, known as immunolents, has been identified. These products are capable of supporting the skin microbiome and skin immunity. An ideal emollient should provide adequate hydration of the stratum corneum and form a barrier that prevents transepidermal water loss. The development and regular use of moisturizers with active ingredients can provide a so-called steroid-sparing effect and reduce dependence on topical corticosteroids.